2001
DOI: 10.1258/0023677011911543
|View full text |Cite
|
Sign up to set email alerts
|

Survival and transmissibility of Pasteurella pneumotropica

Abstract: SummarySurvival has been determined for Pa ste ure lla pne um o tro pic a on various surfaces found in an anim al room at 23 1 C and 50 10% relati ve humidity. Longest survival (120 min) was found on mouse hair, shortest ( < 30 min) on laborat ory coat fabric . Transmission experiments were performed using sentinel animals in order to evaluate the efficiency of their use for the detection of P. pne um o tro pi ca in quaran tined mice. In sentinels exposed to infected mice by close contact, P. pne um o tro pic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…On gram stain (Figure 6b), the pulp chamber contained both gram-positive cocci and gram-negative coccobacilli that were identified as Streptococcus mitus and Pasteurella pneumotropica , respectively, bacteria common in oral flora of humans and rodents. 28,29 There was severe periodontal disease characterized by periapical abscesses; inflammation extended through the apical foramen into the periradicular tissue, causing destruction of roots and alveolar bone (Figure 6c). TRAP stains confirmed extensive osteoclast-mediated bone loss around the roots (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%
“…On gram stain (Figure 6b), the pulp chamber contained both gram-positive cocci and gram-negative coccobacilli that were identified as Streptococcus mitus and Pasteurella pneumotropica , respectively, bacteria common in oral flora of humans and rodents. 28,29 There was severe periodontal disease characterized by periapical abscesses; inflammation extended through the apical foramen into the periradicular tissue, causing destruction of roots and alveolar bone (Figure 6c). TRAP stains confirmed extensive osteoclast-mediated bone loss around the roots (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of subcultured bacterial colonies by matrix-assisted laser desorption/ionization-time of flight mass spectrometry offers good specificity; however, this method is expensive and lacks appropriate murine datasets. Additionally, serological tests are inappropriate for diagnosis of Pasteurellaceae infections, given that seroconversion of sentinel mice exposed to contaminated bedding or cohabitating with infected mice is unreliable [ 8 ]. There are also PCR-based options available for detection and differentiation of rodent-specific Pasteurellaceae : a genus-specific PCR assay to detect all Pasteurellaceae [ 9 ], species-specific assays to detect either of the P .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, experimental contact infection of P. pneumotropica in mice has not been reported previously. However, investigators have reported the transmission of P. pneumotropica [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports of experimental intranasal inoculation models of P. pneumotropica; however, these models might not resemble natural infection [4,11,12] Experimental contact infection resembles natural infection more so than experimental inoculation models [13,14]. There have been some studies on the transmission of this species; however, to our knowledge, experimental contact infection of P. pneumotropica has not been reported [15,16]. In our previous study, NOD/shiJicscid/Jcl mice with multiple defects in adaptive and non-adaptive immunological functions were intranasally infected with bacteria [7].…”
Section: Introductionmentioning
confidence: 99%